2024
DOI: 10.3390/antibiotics13030262
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 Pandemic Rebound of Macrolide-Resistant Mycoplasma pneumoniae Infection: A Descriptive Study

Fan-Fan Xing,
Kelvin Hei-Yeung Chiu,
Chao-Wen Deng
et al.

Abstract: The rebound characteristics of respiratory infections after lifting pandemic control measures were uncertain. From January to November 2023, patients presenting at a teaching hospital were tested for common respiratory viruses and Mycoplasma pneumoniae using a combination of antigen, nucleic acid amplification, and targeted next-generation sequencing (tNGS) tests. The number and rate of positive tests per month and clinical and microbiological characteristics were analyzed. A rapid rebound of SARS-CoV-2 was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A2063G mutations were detected in domain V of 23S rRNA gene in a single-site study in Wuhan, China, during the COVID-19 pandemic between October 2020 and March 2022 [ 35 ]. Another single-site study reported that the A2063G mutation was overwhelmed in this winter outbreak of MPI in China [ 36 ]. However, the representativeness of these studies was restricted by single-site design, and the feature of macrolide-resistance-mutation in the current resurgence remained unclear compared to previous prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…A2063G mutations were detected in domain V of 23S rRNA gene in a single-site study in Wuhan, China, during the COVID-19 pandemic between October 2020 and March 2022 [ 35 ]. Another single-site study reported that the A2063G mutation was overwhelmed in this winter outbreak of MPI in China [ 36 ]. However, the representativeness of these studies was restricted by single-site design, and the feature of macrolide-resistance-mutation in the current resurgence remained unclear compared to previous prevalence.…”
Section: Discussionmentioning
confidence: 99%